PRACTICING PRONUNCIATION THROUGH ENGLISH SONGS FOR ENGLISH STUDENTS - Rafikah Rafikah; Indah Yunita Br. Sitorus (EXCELLENCE: Journal of English and English Education, 2023)
Some teachers may not proficient in teaching pronunciation. Mostly they tend to prioritize the reading, grammar, or writing over pronunciation practice. It results the students' ability to pronounce words are low and they struggle to pronounce the words provided by the teacher correctly. This article aims to assist teachers in pronunciation class by utilizing English songs as the media. English songs can be employed to all levels. It is hoped that by employing English songs in the teaching and learning process of pronunciation, the students will be able to enhance their pronunciation in enjoyable way.